Alveolar macrophage modulation via the gut–lung axis in lung diseases - Chen, Zijian; Liu, Yangqi; Huang, Weizhe (Frontiers in Immunology, 2023)
Several studies have demonstrated great potential implications for the gut–lung axis in lung disease etiology and treatment. The gut environment can be influenced by diet, metabolites, microbiotal composition, primary diseases, and medical interventions. These changes modulate the functions of alveolar macrophages (AMs) to shape the pulmonary immune response, which greatly impacts lung health. The immune modulation of AMs is implicated in the pathogenesis of various lung diseases. However, the mechanism of the gut–lung axis in lung diseases has not yet been determined. This mini-review aimed to shed light on the critical nature of communication between the gut and AMs during the development of pulmonary infection, injury, allergy, and malignancy. A better understanding of their crosstalk may provide new insights into future therapeutic strategies targeting the gut–AM interaction.